2021
DOI: 10.1038/s41598-021-91986-7
|View full text |Cite
|
Sign up to set email alerts
|

Production of basil (Ocimum basilicum L.) under different soilless cultures

Abstract: The main aim of this paper was to investigate the possibility of growing basil under three soilless systems (aeroponic, hydroponic and peatmoss slab systems). A model was developed to predict the nutrients consumption by basil plants. Shoot and root height, fresh and dry mass of whole plant, nutrients uptake, and oil content were studied during the growth period (after 4 and 7 weeks from transplanting). The results indicated that the shoot lengths of basil plants were 71.67 ± 2.89, 65.67 ± 1.15 and 62.33 ± 2.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Khater et al [20] showed that the shoot of basil plants grown in aeroponic (62.00 ± 2.65 cm) was taller than those of hydroponic system (57.83 ± 7.42 cm) and peatmoss slabs (48.77 ± 2.89 cm) at the vegetative and flowering stages after 4 weeks. They also confirmed that the aeroponically grown plants had higher fresh and dry mass of shoot when compared to other two systems.…”
Section: Discussionmentioning
confidence: 99%
“…Khater et al [20] showed that the shoot of basil plants grown in aeroponic (62.00 ± 2.65 cm) was taller than those of hydroponic system (57.83 ± 7.42 cm) and peatmoss slabs (48.77 ± 2.89 cm) at the vegetative and flowering stages after 4 weeks. They also confirmed that the aeroponically grown plants had higher fresh and dry mass of shoot when compared to other two systems.…”
Section: Discussionmentioning
confidence: 99%
“…The plant-growth medium contained 40% coco-peat, 40% perlite, 10% peat moss, and 10% vermiculate. According to Khater et al (2021), it was considered a suitable nutrient substrate. Irrigation and fertilisation were carried out alternately every 4 days.…”
Section: Methodsmentioning
confidence: 99%
“…O. basilicum is used to manage lung disorders and dyspnea in Iran ( Noumi, 2009 ); asthma in Cameroon ( Nath et al, 2008 ); bronchitis, cough, and asthma in India ( Lemos et al, 2016 ); acute lung diseases, including bronchitis, cough, and sore throat, in Brazil ( Janbaz et al, 2014 ); and tuberculosis and acute lung diseases in Ethiopia ( Fujita et al, 1999 ). The bioactive ingredients of the plant depend on the growth regions ( Driesen et al, 2021 ; Khater et al, 2021 ). The effects of O. basilicum and its derivatives on dermal pathology and wound healing including acne, eczema, boils, psoriasis, and rashes were reported ( Fritea et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%